Genome-wide prediction of conserved and nonconserved enhancers by histone acetylation patterns - Roh, Tae-young; Wei, Gang; Farrell, Catherine M.; Zhao, Keji (Genome Research, 2007)
Comparative genomic studies have been useful in identifying transcriptional regulatory elements in higher eukaryotic genomes, but many important regulatory elements cannot be detected by such analyses due to evolutionary variations and alignment tool limitations. Therefore, in this study we exploit the highly conserved nature of epigenetic modifications to identify potential transcriptional enhancers. By using a high-resolution genome-wide mapping technique, which combines the chromatin immunoprecipitation and serial analysis of gene expression assays, we have recently determined the distribution of lysine 9/14-diacetylated histone H3 in human T cells. We showed the existence of 46,813 regions with clusters of histone acetylation, termed histone acetylation islands, some of which correspond to known transcriptional regulatory elements. In the present study, we find that 4679 sequences conserved between human and pufferfish coincide with histone acetylation islands, and random sampling shows that 33% (13/39) of these can function as transcriptional enhancers in human Jurkat T cells. In addition, by comparing the human histone acetylation island sequences with mouse genome sequences, we find that despite the conservation of many of these regions between these species, 21,855 of these sequences are not conserved. Furthermore, we demonstrate that about 50% (26/51) of these nonconserved sequences have enhancer activity in Jurkat cells, and that many of the orthologous mouse sequences also have enhancer activity in addition to conserved epigenetic modification patterns in mouse T-cell chromatin. Therefore, by combining epigenetic modification and sequence data, we have established a novel genome-wide method for identifying regulatory elements not discernable by comparative genomics alone.
10.1101/gr.5767907